PENGARUH LOAN BOOK VALUE, LOAN FAIR VALUE, BOOK VALUE PER SHARE, EARNING PER SHARE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA BANK UMUM DI KOTA LHOKSEUMAWE - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2020)
This study aims to examine the effect of loan book value, loan fair value, book value per share, Earning Per Share and Company Size on firm value at commercial banks in Lhokseumawe City. In this study, based on research results in multiple linear regression analysis, loan book value, loan fair value, book value per share, Earning Per Share and Company Size have a very close relationship with firm value at commercial banks in Lhokseumawe City. The results of the research simultaneously show that loan book value, loan fair value, book value per share, Earning Per Share and Company Size simultaneously affect the firm value at Commercial Banks in Lhokseumawe City and based on the results of the partial test it is known that the variable company size is the dominant factor affecting the value of the Commercial Bank in Lhokseumawe City. It is expected that the company maintains its loan book value, loan fair value, book value per share, Earning Per Share and Company Size within the company in order to be able to increase the company value better.